A Novel Indolizine Derivative Induces Apoptosis Through the Mitochondria p53 Pathway in HepG2 Cells - Yushuang Liu; Yushuang Liu; Enxian Shao; Enxian Shao; Zhiyang Zhang; Zhiyang Zhang; Daji Yang; Guanting Li; Guanting Li; Hua Cao; Hongliang Huang; Hongliang Huang (Frontiers Media S.A., 2019)
Indolizine derivatives are a class of compounds with excellent biological activity. In this study, a series of indolizine derivatives, compound 1 (C1), compound 2 (C2), compound 3 (C3), and compound 4 (C4), were synthesized. 3-(4,5-dimethylthiazole)-2,5-diphenyltetraazolium bromide (MTT) assay was used to evaluate their cytotoxicity against HepG2 (p53-wild), A549, and HeLa cell lines. HepG2 cells apoptosis induced by C3 was determined using Hoechst staining and acridine orange/ethidium bromide staining. Cells' apoptotic ratio was measured by Annexin V-FITC/PI double staining. Changes in mitochondrial membrane potential and intracellular reactive oxygen species (ROS) in HepG2 cells after C3 treatment were determined. Immunofluorescence staining and Western blot analysis were carried out to detect p53 levels and analyze the apoptosis-associated proteins, respectively. Moreover, the cytotoxic activity of C3 was examined in two other hepatocellular carcinoma (HCC) cell lines with different p53 status including Huh-7 cells (p53-mutant) and Hep3B cells (p53-null). The results indicated that C3 showed stronger inhibition towards HepG2 cells than other cell lines. Fluorescent staining and flow cytometry analysis confirmed that C3 induced apoptosis of HepG2 cells. C3 could also increase intracellular ROS and cause a decrease in the mitochondrial membrane potential. C3 promoted p53 activation and increased p53 accumulation in nuclei. The expression of p53 and Bax was increased with the down-regulation of Bcl-2, which promoted the release of cytochrome c and caspase-3 activation. Collectively, the study demonstrated that C3 caused HepG2 cell apoptosis via the mitochondria p53 pathway. These results inspired us to further develop indolizine derivatives as potential potent inhibitors against liver cancer.